Exploratory Factors Analysis of Characteristics of Graduates in Accounting By Establishment’s Requirement in Rayong Province - Phumsiri, Dr. Nattapol (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2025)
The objectives of this study were to: 1. study the characteristics of accounting graduates according to the needs of business establishments in Rayong Province, and 2. Investigate the Exploratory Factor Analysis of the characteristics of accounting graduates according to the needs of business establishments in Rayong Province. The population used in the research was 2,542 factories in Rayong Province. For the sample group, the researcher determined the size according to the Comrey and Lee concept by selecting 500 factories and using the purposive sampling method. The sample representatives who answered the questionnaires were the heads of accounting graduates working in the establishments. The statistics used for data analysis included percentage, mean, standard deviation, and Exploratory Factor Analysis. The research results found that 1. The level of importance of the characteristics of accounting graduates according to the needs of business establishments in Rayong Province was overall at a high level of importance. 2. The appropriate value of the correlation matrix between variables (KMO) was = .979. The result of factor analysis of the survey showed 4 components: (1) Analytical and Interpersonal Skills with a weight of .699; (2) Morality and Ethics with a weight of .771; (3) Knowledge with a weight of .730; and (4) Intellectual Skills with a weight of .672. The model of factor analysis of graduate characteristics passed the evaluation criteria and was consistent with empirical data. This research is beneficial to graduates in preparing them to enter the workforce with quality and efficiency.